Isolation, Purification and Characterization of Pectinase enzyme from Streptomyces thermocarboxydus - Priyanka S Bharadwajand Prajna M Udupa (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2019)
Pectinases, commonly referred to as pectic enzymes, are an important class of enzymes for their uses in industries like wine, paper, and food for the processing of fruits, vegetables, tea, coffee, and can be extracted from actinomycetes, a group of bacteria popular for research for such products as the penicillin and pectinases. Such pectinase enzymes that will work at high temperatures and at appropriate pH conditions can be of benefit at high temperatures, which can be used to speed up these processes. Speed of processing gives an economic gain in commercial applications. This study involved the isolation, purification and characterisation of pectinase enzyme from Streptomyces thermocarboxydus. Soil bacterial isolation resulted in seventeen different types of colonies and these from petri were transferred to agar and cultured on pectin containing media at 37° C temperature, and t 8080736856 he strain showing maximum pectin clearing detected with iodine vapour. The selected isolate was first sent for sequencing using rRNA technology and phylogenetic analysis. Experiments for culture optimization and enzyme characterization were carried out. The optimum pH and temperature for culture was found out to be 4 and 50 ˚C, and for the partially purified enzyme, maximum activity, at neutral and alkaline pH and 60 ˚C. Hence, this enzyme proves to be a promising candidate for commercial applications.